2013
DOI: 10.4103/1305-7456.110174
|View full text |Cite
|
Sign up to set email alerts
|

Is the 810-nm diode laser the best choice in oral soft tissue therapy?

Abstract: Objective:To evaluate the safety and efficacy of an 810-nm diode laser for treatment of benign oral soft tissue lesions.Materials and Methods:Treatment with the 810-nm diode laser was applied to a group of eighteen patients with pathological frenulum and epulis fissuratum; five patients with oral lichen planus, oral leukoplakia, and mucous membrane pemphigoid; and four patients with pyogenic granuloma.Results:Although the conventional surgery wound heals in a fairly short time, in the present study, the simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
64
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 25 publications
7
64
1
2
Order By: Relevance
“…Today this radiological examination is increasingly replaced by dynamic MRA, which is much less invasive [7,9].…”
Section: Discussionmentioning
confidence: 99%
“…Today this radiological examination is increasingly replaced by dynamic MRA, which is much less invasive [7,9].…”
Section: Discussionmentioning
confidence: 99%
“…Like Nd:YAG and CO 2 lasers, diode lasers have the capability to cut or to vaporize soft tissues. 33,39,40 In addition, Janda et al 41 pointed out that diode laser had low thermal effect on depth of carbonized zones at the surface of the tissue in histological examination. Although in our study the depth of carbonized zone would be negligible due to the lesion's large size, likewise we observed similar findings too.…”
Section: Discussionmentioning
confidence: 99%
“…Recently several other researchers preferred diode laser when performing excision of PGs. 2,3,33,34 In our case we chose diode laser because it ensures relatively bloodless surgical field, which is crucial in these hemorrhagic lesions, improves hemostasis and coagulation, and leaves minimal swelling and scarring after surgery. Several studies have reported that after simple excision, recurrence occurs in up to 16% of lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations